A review of the aftercare module from the perspective of the Kuala Lumpur treatment and rehabilitation center staff - Mohamad Murad, Nurfatin Afza; Ma’rof, Aini Azeqa; Wan Jaafar, Wan Munira; Mohd Khir, Azlina (Human Resource Management Academic Research Society, 2022)
Based on a preliminary study, this paper aims to describe the aftercare module at a Drug Treatment and Rehabilitation Center in Kuala Lumpur. The significance of this study lies in its ability to provide an overview of the treatment utilised for drug abuse survivors following rehabilitation. This is referred to as an "aftercare programme." The rehabilitation process at this treatment and rehabilitation centre is guided by the psycho-socio-bio-spiritual model. After completing the institution's rehabilitation programme, the aftercare programme consists of regular meetings in which issues and difficulties are discussed. Qualitative approaches were used as the methodology for this paper. Observational data collection did not participate in the sessions of the aftercare module or in-depth interviews with the officers responsible for the aftercare module's operation. This preliminary study reveals that the aftercare programme approach that emphasises the concept of Help Support Group and the 12 steps of Narcotics Anonymous aids ex-addicts in their recovery, particularly in the areas of behaviour formation and emotional support. Therefore, additional research on the aftercare programme should provide more details and an overview of the programme from the perspective of a drug addict.